A rare case of giant cell tumor in navicular bone: a case report - Taraviya, Abhishek K.; Patel, Jyotish G.; Patel, Ankit R. (International Journal of Research in Orthopaedics, 2024)
Giant cell tumor (GCT) is a benign but locally aggressive lesion of the bone. They are common in skeletally mature individuals with a slight female preponderance. Rare unusual presentations can occur. This case report describes a rare case of GCT of bone in the right navicular bone in a 25-year-old male patient who presented with complaints of pain and swelling in right foot and difficulty in walking. The diagnosis was made with radiological investigations and was then confirmed with histopathological evaluation. The lesion was managed with extensive curettage and bone grafting. Patient had complete resolution of symptoms post-surgery with no signs of local recurrence at 18-months follow-up.